Effectiveness of three commonly used transition phase diets in the inpatient management of children with severe acute malnutrition: a pilot randomized controlled trial in Malawi - Christian J. Versloot; Wieger Voskuijl; Sara J. van Vliet; Meta van den Heuvel; Jane C. Carter; Ajib Phiri; Marko Kerac; Geert Tom Heikens; Patrick F. van Rheenen; Robert H. J. Bandsma (BMC, 2017)
Abstract Background The case fatality rate of severely malnourished children during inpatient treatment is high and mortality is often associated with diarrhea. As intestinal carbohydrate absorption is impaired in severe acute malnutrition (SAM), differences in dietary formulations during nutritional rehabilitation could lead to the development of osmotic diarrhea and subsequently hypovolemia and death. We compared three dietary strategies commonly used during the transition of severely malnourished children to higher caloric feeds, i.e., F100 milk (F100), Ready-to-Use Therapeutic Food (RUTF) and RUTF supplemented with F75 milk (RUTF + F75). Methods In this open-label pilot randomized controlled trial, 74 Malawian children with SAM aged 6-60 months, were assigned to either F100, RUTF or RUTF + F75. Our primary endpoint was the presence of low fecal pH (pH ≤ 5.5) measured in stool collected 3 days after the transition phase diets were introduced. Secondary outcomes were duration of hospital stay, diarrhea and other clinical outcomes. Chi-square test, two-way analysis of variance and logistic regression were conducted and, when appropriate, age, sex and initial weight for height Z-scores were included as covariates. Results The proportion of children with acidic stool (pH ≤5.5) did not significantly differ between groups before discharge with 30, 33 and 23% for F100, RUTF and RUTF + F75, respectively. Mean duration of stay after transitioning was 7.0 days (SD 3.4) with no differences between the three feeding strategies. Diarrhea was present upon admission in 33% of patients and was significantly higher (48%) during the transition phase (p < 0.05). There was no significant difference in mortality (n = 6) between diets during the transition phase nor were there any differences in other secondary outcomes. Conclusions This pilot trial does not demonstrate that a particular transition phase diet is significantly better or worse since biochemical and clinical outcomes in children with SAM did not differ. However, larger and more tightly controlled efficacy studies are needed to confirm these findings. Trial registration ISRCTN13916953 Registered: 14 January 2013.